Exodus International: Banned Apps, App Stores, and the Politics of Visibility - Gillespie, Tarleton (Appified: Culture in the Age of Apps (Jeremy Morris and Sarah Murray, eds), 2018)
While Apple promises a fair and impartial review process, in decisions like the one they faced about the Exodus International app there is no choice they could make that is not political. As a consequence, they are increasingly being taken to task for how they curate the public space of apps.